Microstructure and mechanical properties of additively manufactured high strength low alloy steel - Neo, Jer Ruey (Nanyang Technological University, 2020)
Additive manufacturing, known as 3D printing, is one of the potential transformations to the industrial revolution. It is a process that allows many companies to produce intricate complex components. The parts produced are strong and make use of data directly pulled from the computer aided design (CAD) software. The benefits of additive manufacturing allow the marine & offshore (M&O) industries in Singapore to provide marine supply components and to further improve Singapore’s position as an important hub in the world. The M&O industries makes use of High Strength Low alloy steels such as API 5L X65 and ASTM A131 EH36 due to their exceptional material properties that fit in well for the industries. However, even with the above-mentioned advantages, all processes and materials will have their limitations. Defects may occur in the materials during the additive manufacturing process which is caused by factors such as composition of the materials, scan pattern and temperature that will greatly affect the quality of final products. The initiating factors of the additive manufacturing will create defects such as lack of fusion, inclusion of foreign atoms, heat affected zone, etc. The project objective is to study the microstructure and mechanical properties of high strength low alloy steel samples printed using direct laser deposition process. The project will mainly focus on the two materials, namely API 5L X65 powder and wire. The two-filler materials were additively manufactured in four different directions, consisting of XY−0°, XZ−90°, −45°, −45°. Tensile and Charpy impact test were conducted on the two filler materials, which were in accordance to the ASTM standards. The Tensile tests followed the ASTM E8 and the Charpy impact tests followed the ASTM E23. Stress/Strain curves were plotted and analysed accordingly using the tensile test results. The test results from this study were compared with the previous results obtained from the powder filler material by a previous FYP student. A systematic investigation of the microstructures and fractography of the two printed steel materials was performed after the mechanical tests were made. The microstructures of the printed materials were examined by using two different sample preparation methods, i.e, polishing followed by etching and polishing without etching. The etched sample were viewed via optical microscopy. The unetched samples were viewed via both optical microscope and scanning electron microscope (SEM). The fractured surfaces of the samples after the two kind of mechanical tests were examined mainly using SEM.